VISUAL DICTIONARIES AS A MULTIMODAL LEXICOGRAPHIC SYSTEM: LINGUISTIC MECHANISMS OF MEANING REPRESENTATION (Journal of Universal Science Research, 2026)
This study looks at visual dictionaries as a separate class of lexicographic models and explores the language processes that control how meaning is represented in them. Visual dictionaries create meaning through a methodical interaction between lexical nomination and visual representation, in contrast to traditional explanatory dictionaries that mostly employ vocal definitions. The paper examines the functions of iconic mapping, nominative anchoring, spatial structuring, and contextual framing as essential mechanisms of semantic formation and offers a novel multi-layer model of visual-semantic integration. The study is located in the field of comparative lexicography (10.00.06) and combines cognitive linguistics, multimodal theory, and functional lexicography. The findings demonstrate that visual dictionaries constitute a unique kind of lexicography with iconic-semantic mapping, spatial structuralization of lexical relations, and cognitive optimization of semantic access. The paper advances theoretical lexicography by formalizing visual-semantic integration as a distinct language mechanism.